Remote laboratories in teaching and learning – issues impinging on widespread adoption in science and engineering education - Cooper, Martyn (International Journal of Online and Biomedical Engineering (iJOE), 2005)
This paper discusses the major issues that impinge on the widespread adoption of remote controlled laboratories in science and engineering education. This discussion largely emerges from the work of the PEARL1 project and is illustrated with examples and evaluation data from the project. Firstly the rationale for wanting to offer students remote experiments is outlined. The paper deliberately avoids discussion of technical implementation issues of remote experiments but instead focuses on issues that impinge on the specification and design of such facilities. This includes pedagogic, usability and accessibility issues. It compares remote experiments to software simulations. It also considers remote experiments in the wider context for educational institutions and outlines issues that will affect their decisions as to whether to adopt this approach. In conclusion it argues that there are significant challenges to be met if remote laboratories are to achieve a widespread presence in education but expresses the hope that this delineation of the issues is a contribution towards meeting these challenges.